Analisis Yuridis Tindak pidana Illegal Fishing yang Dihubungkan oleh Undang-Undang 45 Tahun 2009 Tentang Perubahan atas Undang-Undang 31 Tahun 2004 Tentang Perikanan - Akmal Fauzan (Bandung Conference Series: Law Studies, 2022)
Abstract Law of the Republic of Indonesia Number 45 of 2009 concerning Fisheries Article 1 Paragraph 1 states that fisheries are all activities related to the management and utilization of fish resources and their environment. Illegal fishing is fishing activity carried out by a country or foreign ship in waters that are not under its jurisdiction without permission from a country that has jurisdiction or the fishing activity is contrary to the laws and regulations of that country. According to the Food and Agriculture Organization (hereinafter referred to as FAO), illegal fishing has caused a total loss of up to US$75-125 billion worldwide, of which 16-26 percent is the loss experienced by Indonesia. According to observers, illegal and unreported fishing occurs in various fishing centers in the world and can reach 30% of the total catch. There are several examples of cases that occurred in the province of North Sulawesi, namely fisheries crimes that occurred in the border areas of the Philippines and Malaysia, Sangihe, Talaud, and Sebatik areas in Kalimantan. The prevalence of illegal fishing in the province of North Sulawesi is shown by the data on the number of cases of illegal fishing that were examined at the Bitung Fisheries Court. There are 77 cases with details: In 2010 there were 12 cases, in 2011 there were 6 cases, in 2012 there were 24 cases, in 2013 there were 23 cases, in 2014 there were 6 cases, and in 2015 (until April 13 2015) there were as many as 3 cases, while there are 2 cases that are appealed, there are 1 cassation, and there is 1 case that is requested for reconsideration. Fisheries crimes that occur in Indonesian waters can occur if fishermen or fish entrepreneurs or Indonesian-flagged vessels or foreign fishing vessels operating in the ZEEI do not have a Fishing Permit (SIPI). Foreign-flagged fishing vessels that do not have SIPI while in WPRI are required to keep fishing gear in their vessels. The application of criminal sanctions against perpetrators of illegal fishing has been implemented in accordance with the provisions of Law No. 45 of 2009. The fisheries law threatens perpetrators with severe criminal witnesses. In the Fisheries Law, the threat of criminal sanctions is specifically regulated in Chapter XV concerning criminal provisions starting from Article 84 to Article 104 of the Fisheries Law. Indonesia has an effort in dealing with the problem of illegal fishing in the ZEEI according to the Ministerial Decree number KEP/50/MEN/2012 as a form of implementation of the code of conduct for responsible fisheries (CCRF) which was agreed in 1995 by FAO countries on fisheries management and development. orderly, responsible, Lack of public awareness about the criminal act of Illegal fishing which can harm the natural resources in the sea. Keywords: constitution,Illegal Fishing,criminal law Abstrak. Undang-Undang Republik Indonesia Nomor 45 Tahun 2009 tentang Perikanan Pasal 1 Ayat 1 menyatakan bahwa perikanan adalah semua kegiatan yang berhubungan dengan pengelolaan dan pemanfaatan sumber daya ikan dan lingkungannya. Adapun illegal fishing adalah kegiatan penangkapan ikan yang dilakukan oleh suatu negara atau kapal asing di perairan yang bukan merupakan yuridiksinya tanpa izin dari negara yang memiliki yuridiksi atau kegiatan penangkapan ikan tersebut bertentangan dengan hukum dan peraturan negara itu. Berdasarkan Food and Agriculture Organization (selanjutnya disebut FAO) penangkapan illegal fishing telah menyebabkan total kerugian hingga 75-125 miliar US dolar diseluruh dunia, dengan 16-26 persennya merupakan kerugian yang dialami Indonesia. Menurut pengamat, penangkapan ikan illegal maupun yang tidak dilaporkan terjadi di berbagai sentra penangkapan ikan dunia dan dapat mencapai 30% dari total tangkapan. Ada beberapa contoh kasus yang terjadi di provinsi Sulawesi Utara, yakni tindak pidana perikanan yang terjadi di daerah perbatasan Filipina dan Malaysia, daerah Sangihe, Talaud, dan daerah Sebatik di Kalimatan. Maraknya terjadinya tindak pidana illegal fishing di provinsi Sulawesi Utara ditunjukan oleh data jumlah kasus tindak pidana illegal fishing yang di periksa di pengadilan perikanan Bitung. Ada sebanyak 77 perkara dengan rincian: Pada tahun 2010 ada 12 perkara, tahun 2011 ada 6 perkara, tahun 2012 ada 24 perkara, tahun 2013 ada 23 perkara, tahun 2014 ada 6 perkara, dan pada tahun 2015 (sampai dengan 13 april 2015) ada sebanyak 3 perkara, sedangkan perkara yang naik banding ada 2, kasasi ada 1, dan ada 1 perkara yang dimintakan peninjauan kembali. Tindak pidana perikanan yang terjadi di perairan Indonesia dapat terjadi bila nelayan atau pengusaha ikan atau kapal berbendera Indonesia maupun kapal ikan asing yang beroperasi di ZEEI tidak memiliki Surat Izin Penangkapan Ikan (SIPI). Bagi kapal penangkapan ikan berbendera asing yang tidak memiliki SIPI selama berada WPRI wajib menyimpan alat tangkap ikan di dalam kapal-kapalnya. Penerapan sanksi pidana terhadap pelaku illegal fishing sudah diterapkan sesuai dengan ketetuan menurut Undang–Undang nomor 45 tahun 2009. Undang-Undang perikanan mengancam pelaku dengan saksi pidana yang berat. Dalam Undang-Undang Perikanan, ancaman sanksi pidana diatur secara khusus dalam bab XV tentang kententuan pidana mulai pasal 84 sampai dengan pasal 104 UU Perikanan. Indonesia memiliki upada dalam menangani masalah illegal fishing di ZEEI sesuai keputusan Menteri nomor KEP/50/MEN/2012 sebagai bentuk penerapan dari the code of conduct for responsible fisheries (CCRF) yang disepakati pada tahun 1995 oleh negara-negara FAO tentang pengelolaan dan pembangunan perikanan yang tertib, bertanggung jawab, ​Kurangnya kesadaran masyarakat tentang tindak pidana Illegal fishing yang dapat merugikan sumberdaya alam yang ada di laut. Kata Kunci: Undang-Undang,Illegal fishing, Hukum pidana